The Influence of Principals Self Personality Values towards Their Work Culture - Muhammad Asri; Lokman Bin Mohd. Tahir (International Journal of Evaluation and Research in Education (IJERE), 2014)
This study aimed to identify the influence of principals’ self personality values toward teachers’ work culture in high schools. The sample consisted of 34 principals from SMAN, SMKN and MAN in the City of Makassar, South Sulawesi Indonesia. The sample of this study is population sample. The instrument used was a questionnaire. Data were analyzed using Statistical Package for Social application software Science version 20.0. Two statistics were used descriptive statistics including the mean score and inference of linear to test the hypothesis. The reliability (Cronbach Alpha) for the instruments used in this study is 0.879. The results show that honesty and compliance are both top components of self values of principals in implementing principalship at school. There was also a significant influence on self personality values of principals toward teachers’ work culture at school.DOI: http://dx.doi.org/10.11591/ijere.v3i4.6961